Does the foreign market entry mode choice affect export performance? the case of the Spanish hotel industry / Ar įėjimo į užsienio rinką strategijos pasirinkimas turi įtakos eksporto skatinimui? Ispanijos viešbučių sektoriaus pavyzdys - Juan M. Berbel-Pineda; José M. Ramírez-Hurtado (Journal of Business Economics and Management, 2011)
Knowing the factors that affect the export performance has become one of the most recent research lines in the literature relative to business internationalisation. In this sense, several works based on the meta-analysis technique have come up in the two last decades in order to recapitulate the set of studies which have analysed such a topic. Taking these reviews as a starting point, we may establish that there is not a clear relationship between the entry mode and export performance variables. With a study on a sample of 122 Spanish hotels all over the world, we have the intention of analysing the existence and sense of the relationship between both variables. As a conclusion, we may state that the market entry mode has a positive and significant influence on export performance.